2020
DOI: 10.3928/01477447-20200721-10
|View full text |Cite
|
Sign up to set email alerts
|

In-depth Analysis of Adult Reconstruction Fellowship Websites

Abstract: This investigation assessed the availability and comprehensiveness of adult reconstruction fellowship websites. A list of adult reconstruction fellowship programs was compiled using 4 online directories: American Association of Hip and Knee Surgeons, San Francisco Match, Fellowship and Residency Electronic Interactive Database Access, and American Academy of Orthopaedic Surgeons. These directories and Google (Alphabet Inc, Menlo Park, California) searches were used to assess for the presence and functionality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Utilizing methodology consistent with, though more comprehensive than, a 2015 study to facilitate comparison (Silvestre, Guzman, Abbatematteo, While websites are indeed growing increasingly thorough and accessible, many still lack crucial program details and include obsolete information. In 2017, poor content quality and accessibility for foot and ankle (Hinds et al 2016) fellowship websites were found, findings echoed across sports medicine (Yayac, Javandal, and Mulcahey 2017), adult reconstruction (Gu et al 2018;Ahmed et al 2020;Bradley L. Young et al 2018), trauma (B. L. , pediatric orthopaedics (Davidson et al 2014), hand (Silvestre, Guzman, Abbatematteo, et al 2015;Trehan, Morrell, and An updated analysis of the content and accessibility of hand surgery fellowship websites and fellowship dir……”
Section: Discussionmentioning
confidence: 99%
“…Utilizing methodology consistent with, though more comprehensive than, a 2015 study to facilitate comparison (Silvestre, Guzman, Abbatematteo, While websites are indeed growing increasingly thorough and accessible, many still lack crucial program details and include obsolete information. In 2017, poor content quality and accessibility for foot and ankle (Hinds et al 2016) fellowship websites were found, findings echoed across sports medicine (Yayac, Javandal, and Mulcahey 2017), adult reconstruction (Gu et al 2018;Ahmed et al 2020;Bradley L. Young et al 2018), trauma (B. L. , pediatric orthopaedics (Davidson et al 2014), hand (Silvestre, Guzman, Abbatematteo, et al 2015;Trehan, Morrell, and An updated analysis of the content and accessibility of hand surgery fellowship websites and fellowship dir……”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated the deficits in online resources available for fellowship program information. 21 , 22 , 23 With regard to orthopaedic sports medicine fellowships in particular, Yayac et al. 23 found that only 54% of fellowships included a link on the American Orthopaedic Society for Sports Medicine website.…”
Section: Current Orthopaedic Sports Medicine Fellowship Interview Processmentioning
confidence: 99%
“…Gu et al [2] reviewed all programs identified through the AAHKS fellowship program directory in 2018 and found that only 3 of the 78 listed programs had functional links to program websites and that the database lacked key information on program structure, the application process and fellow education. In a recent query of adult reconstruction fellowship program websites available through AAHKS, San Francisco Match, American Academy of Orthopaedic Surgeons, and Google, Ahmed et al [3] report that 19.8% of did not have a functioning website.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent query of adult reconstruction fellowship program websites available through AAHKS, San Francisco Match, American Academy of Orthopaedic Surgeons, and Google, Ahmed et al. [ 3 ] report that 19.8% of did not have a functioning website.…”
Section: Introductionmentioning
confidence: 99%